60 Performance of growing beef cattle consuming bahiagrass hay treated with calcium oxide and molasses. (7th December 2018) - Ciriaco, F; Henry, D; Canal, L; Sanford, C; Barreneche, G; Gomez Luna, A; Peña, M; Dubeux, J; DiLorenzo, N
Abstract: An experiment was conducted to evaluate the effects of bahiagrass ( Paspalum notatum ) hay treated with calcium oxide (CaO) and molasses on performance of growing beef cattle. Ninety-six growing Bos taurus and Bos indicus heifers (250 ± 29 kg of BW) and steers (256 ± 45 kg of BW) were used in a randomized complete block design. The experiment consisted of a 56 d period in which animals were weighed every 14 d. On d 0, animals were weighed after 16-h water and feed withdrawal, stratified by sex, breed, and BW, and blocked by initial BW. Cattle were then allotted to 24 dormant bahiagrass pastures (1.34 ha each; 4 animals/pasture), which were located in 2 different areas within 0.52 km of each other. Pastures were stratified by location and randomly assigned ( n = 8 pastures/treatment) to 1 of 3 treatments: 1) untreated dry hay (DH ); 2) hay treated with 10% molasses (DM basis) + water (to 35% DM; MOL ); or 3) hay treated with 5% CaO (DM basis) + 10% molasses (DM basis) + water (to 35% DM; CaO+MOL ). Data were analyzed using pasture as the experimental unit. The model included the fixed effects of treatment, sex, and their interaction. Location and block were included as random effects. Initial and final BW were not affected by treatment ( P = 0.362, P = 0.283; initial and final BW, respectively) or sex ( P = 0.875, P = 0.495; initial and final BW, respectively) and no treatment × sex interaction was observed ( P > 0.05). Additionally, no effects of treatment ( P = 0.515), sex ( P = 0.868), or treatment × sex interaction ( P = 0.582) were observed on ADG (average of -0.03 kg). In conclusion, bahiagrass hay treated with molasses alone or in combination with CaO failed to improve performance of growing beef cattle.